Whence the Sovereignty?: Disentangling Some Theo‐Political Concepts. (13th January 2019) - Kemp, Matthew
Abstract: This essay challenges an approach to political theology, exemplified by Clayton Crockett, that insists that divine sovereignty must be rejected to avoid the conception of political sovereignty developed by Carl Schmitt. Crockett conflates different understandings of God and God's power, particularly ignoring the rise of nominalism and its influence over modern political theory. By attending to this history, we see that Crockett is incorrect to reject all classical onto‐theological or monotheistic definitions of God as the basis for sovereignty. The final section explores other theological options (Oliver O'Donovan, John Milbank, Jürgen Moltmann) that also challenge modern political sovereignty from within the classical Christian tradition.